(untitled) (Journal of Environmental Science and Natural Resources, 2016)
North Indian Ocean (NIO) is a favorable place for cyclone development where several tropical cyclones form every year. Bangladesh experiences 52 cyclones from 1960 to 2010, where cyclone AILA in 2009 was the most destructive in terms of damage of properties and fatalities. This study assesses the weather anomalies related to cyclone AILA using atmospheric sounding indices. During the formation of AILA the vertical atmospheric column was seriously unstable over NIO. The Sea Surface Temperature (SST) was increased anomalously and persisted over NIO for three consecutive days. The increased SST was one of the major causes to form depression as well as cyclone over NIO. To assess the weather anomalies several atmospheric sounding indices were used. The Skew-T/Log-P diagram showed positive buoyant and a large temperature difference between air parcel (Tp) and environment (Te) on May 23, 2009. Both the temperature increment was very sharp which created dry punch within 650550hPa height zone. The atmospheric sounding indices could be used for cyclone weather forecasting more accurately in this region. J. Environ. Sci. & Natural Resources, 8(2): 21-24 2015